The Relative Importance of Physician Communication, Participatory Decision Making, and Patient Understanding in Diabetes Self-management - Heisler, Michele (Blackwell Science Inc, 2002)
OBJECTIVE: Patients' self-management practices have substantial consequences on morbidity and mortality in diabetes. While the quality of patient-physician relations has been associated with improved health outcomes and functional status, little is known about the impact of different patient-physician interaction styles on patients' diabetes self-management. This study assessed the influence of patients' evaluation of their physicians' participatory decision-making style, rating of physician communication, and reported understanding of diabetes self-care on their self-reported diabetes management. DESIGN: We surveyed 2,000 patients receiving diabetes care across 25 Veterans' Affairs facilities. We measured patients' evaluation of provider participatory decision making with a 4-item scale (Provider Participatory Decision-making Style [PDMstyle]; α = 0.96), rating of providers' communication with a 5-item scale (Provider Communication [PCOM]; α = 0.93), understanding of diabetes self-care with an 8-item scale (α = 0.90), and patients' completion of diabetes self-care activities (self-management) in 5 domains (α = 0.68). Using multivariable linear regression, we examined self-management with the independent associations of PDMstyle, PCOM, and Understanding. RESULTS: Sixty-six percent of the sample completed the surveys (N = 1,314). Higher ratings in PDMstyle and PCOM were each associated with higher self-management assessments (P < .01 in all models). When modeled together, PCOM remained a significant independent predictor of self-management (standardized β: 0.18; P < .001), but PDMstyle became nonsignificant. Adding Understanding to the model diminished the unique effect of PCOM in predicting self-management (standardized β: 0.10; P = .004). Understanding was strongly and independently associated with self-management (standardized β: 0.25; P < .001). CONCLUSION: For these patients, ratings of providers' communication effectiveness were more important than a participatory decision-making style in predicting diabetes self-management. Reported understanding of self-care behaviors was highly predictive of and attenuated the effect of both PDMstyle and PCOM on self-management, raising the possibility that both provider styles enhance self-management through increased patient understanding or self-confidence.